Integrating Tembang Bocah Banyumasan into the PGMI Curriculum for Prospective Elementary School Educators: A Step PGMI Curriculum Towards Decolonizing Music Education - Winangsit, Emah; Sunarto; Udi Utomo; Syahrul Syah Sinaga; Fajry Sub'haan Syah Sinaga; Muhammad Asyraf Mohd Bakri (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study examines the integration of Tembang Bocah Banyumasan into the PGMI curriculum at UIN Saizu Purwokerto as a decolonizing intervention in music education. In the PGMI context, the longstanding dominance of Western music has limited pre-service teachers’ exposure to local musical knowledge, weakened cultural rootedness, and produced learning practices that are insufficiently aligned with Indonesia’s cultural diversity. The paper aims to examine how this integration unfolds through three key phases: critical awareness, reappropriation, and emancipation and knowledge production, where students create and perform works that integrate local culture, Islamic values, and environmental awareness. The research employs a qualitative descriptive approach, analyzing curriculum structure, weekly learning stages, and empirical findings from student engagement. The results indicate that integrating Tembang Bocah Banyumasan fosters cultural identity, critical thinking, and creativity among PGMI students, while also contributing to a more inclusive, contextually relevant curriculum for elementary schools. Challenges, such as limited access to traditional instruments, were addressed through digital tools and local artist collaborations, ensuring a meaningful and adaptable learning experience. The findings suggest that this integration not only decolonizes music education but also bridges the gap between university and elementary school curricula, offering a model for inclusive and culturally responsive teaching.